The challenges of algorithm literacy and innovation diffusion in AI era - Siti Sarah; Ade Budhi Salira; Dina Siti Logayah (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid growth of AI-driven social media platforms has significantly heightened the urgency of algorithmic literacy in K–12 education, yet this competence remains largely absent from Indonesian Social Studies Education. This study examines barriers to the diffusion of algorithmic literacy as an educational innovation within Social Studies Education using Everett Rogers’ Diffusion of Innovations theory as the analytical framework. A PRISMA-based systematic literature review analyzed 42 articles from Scopus, ERIC, Google Scholar, and Dimensions published between 2015 and 2025. Drawing on Rogers’ five innovation attributes, findings reveal that high conceptual complexity, low compatibility with the Merdeka Curriculum Learning Outcomes, minimal trialability due to the absence of ready-to-use instructional modules, and low observability of benefits constitute the primary diffusion barriers. Most Social Studies teachers remain in the late majority or laggard adopter categories due to limited digital competence and institutional inertia. The study concludes that Social Studies Education is the most strategic subject for integrating algorithmic literacy in Indonesian K–12 education given its mandate to develop civic reasoning, democratic values, and critical social thinking. Recommendations include explicit integration of algorithmic literacy competencies in the IPS Learning Outcomes and development of context-based instructional modules. Abstrak Pesatnya pertumbuhan platform media sosial berbasis kecerdasan buatan (Artificial Intelligence/AI) semakin meningkatkan urgensi literasi algoritmik dalam pendidikan K-12. Namun, kompetensi ini masih sangat terbatas dalam pembelajaran IPS Indonesia. Studi ini mengkaji hambatan difusi literasi algoritmik sebagai inovasi pendidikan dalam pembelajaran IPS menggunakan teori Difusi Inovasi Everett Rogers sebagai kerangka analitis. Tinjauan pustaka sistematis berbasis PRISMA menganalisis 42 artikel dari Scopus, ERIC, Google Scholar, dan Dimensions (2015-2025). Berdasarkan lima atribut inovasi Rogers, temuan menunjukkan bahwa tingginya kompleksitas konseptual, rendahnya kompatibilitas dengan Capaian Pembelajaran Kurikulum Merdeka, minimnya trialability, dan rendahnya observabilitas manfaat merupakan hambatan difusi utama. Sebagian besar guru IPS berada pada kategori mayoritas akhir atau tertinggal akibat keterbatasan kompetensi digital dan inersia institusional. Studi ini menyimpulkan bahwa pembelajaran IPS merupakan lokus paling strategis untuk mengintegrasikan literasi algoritmik dalam pendidikan K-12 di Indonesia, mengingat mandatnya untuk mengembangkan penalaran kewargaan, nilai-nilai demokratis, dan berpikir kritis sosial. Rekomendasi mencakup integrasi kompetensi literasi algoritmik secara eksplisit dalam Capaian Pembelajaran IPS serta pengembangan modul ajar berbasis konteks. Kata Kunci: difusi inovasi; era AI; kewarganegaraan digital; literasi algoritma; pembelajaran IPS